2022
DOI: 10.3389/fendo.2022.966344
|View full text |Cite
|
Sign up to set email alerts
|

Infectious diseases associated with pediatric type 1 diabetes mellitus: A narrative review

Abstract: Diabetes mellitus (DM) has been frequently associated with an impaired immune response against infectious agents, making affected patients at risk for more severe disease and sometimes causing worse outcomes. The recent COVID-19 pandemic has seriously affected patients with both diabetes, in particular those carrying comorbidities or with poor glycemic control. As regards pediatric diabetes mellitus, the availability of more accurate and technological tools for glycemic management and the improved markers of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 141 publications
0
6
0
Order By: Relevance
“…One of the largest studies to date on infections in T1DM used the Australian diabetes register and showed elevated mortality from septicemia and osteomyelitis among individuals with T1DM [ 8 ]. DM is frequently associated with an impaired immune response against infectious agents due to microangiopathy and direct impairment of the function of immune system cells, putting affected patients at risk for more severe infectious disease courses, especially those with poorer glycemic control or carrying comorbidities [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the largest studies to date on infections in T1DM used the Australian diabetes register and showed elevated mortality from septicemia and osteomyelitis among individuals with T1DM [ 8 ]. DM is frequently associated with an impaired immune response against infectious agents due to microangiopathy and direct impairment of the function of immune system cells, putting affected patients at risk for more severe infectious disease courses, especially those with poorer glycemic control or carrying comorbidities [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…To summarize, although the literature is discordant, the evidence of a potential role of SARS-CoV-2 in T1D onset and DKA frequency in newly diagnosed and known T1D diabetes is quite consistent, which deserves further investigation to understand the underlying responsible mechanisms. It is well known that some viral infections, especially rubella, Coxsackie, mumps, enterovirus, and the Epstein–Barr virus, represent important environmental risk factors for the development of T1D [ 171 , 172 ]. Since the start of the SARS-CoV-2 pandemic, attention has been paid on this novel virus as a further infective cause in the development and progression of T1D [ 173 ].…”
Section: Diabetesmentioning
confidence: 99%
“…Hyperglycemia and insulin deficiency reduce key mediators of innate humoral and cell‐mediated immune responses to various pathogens, including fungi, and decrease synthesis of inflammatory cytokines 2 . Hyperglycemia increases nutrients for Candida and activity of acid protease, an enzyme that promotes fungal adhesion to epithelial cells, increasing the likelihood of Candida colony formation 3 .…”
Section: Figurementioning
confidence: 99%